ON THE METHODOLOGY OF THE DESIGN OF TRANSPORT AND ECONOMIC BALANCE - E. A. Zhukov; A. I. Fedorenko (Модернизация, инновация, развитие)
The article contains a critical analysis of existing methods of forecasting of volumes of transport services on the basis of the analysis of the dynamics of volumes of commodity flows at the regional and Federal levels. The recommendations on use of different methods of forecasting for the development of transport and economic balance are presented.